2012
DOI: 10.4088/jcp.12m07946
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Psychiatric Disorders in Middle-Aged and Older Adults

Abstract: The prevalence of childhood sexual abuse in this sample was comparable to the prevalence rates identified in previous studies. The associations of childhood sexual abuse and revictimization with a wide range of psychiatric disorders raises further questions about the underlying mechanisms in the elderly. This study also supports the notion that childhood sexual abuse and revictimization are associated with a higher rate of utilization of mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 0 publications
5
42
0
3
Order By: Relevance
“…In a study of older adults, Beautrais (2002) found that those with serious suicidal behavior (death by suicide or medically serious attempts) were more likely than comparison subjects to have been exposed to childhood sexual abuse. In another study of older adults (Chou, 2012) sexual abuse was associated with past-year suicidal ideation (sexually abused OR D 6.2 versus non-abused OR D 2.4, CI D 1.5 to 4.95) but not past-year suicide attempts. In a large study of older adults, Draper et al (2008) found physical and sexual abuse to be associated with lifetime suicide attempts.…”
Section: Ace and Suicidementioning
confidence: 92%
“…In a study of older adults, Beautrais (2002) found that those with serious suicidal behavior (death by suicide or medically serious attempts) were more likely than comparison subjects to have been exposed to childhood sexual abuse. In another study of older adults (Chou, 2012) sexual abuse was associated with past-year suicidal ideation (sexually abused OR D 6.2 versus non-abused OR D 2.4, CI D 1.5 to 4.95) but not past-year suicide attempts. In a large study of older adults, Draper et al (2008) found physical and sexual abuse to be associated with lifetime suicide attempts.…”
Section: Ace and Suicidementioning
confidence: 92%
“…Early life trauma, including sexual and physical abuse, has also been identified as a risk factor for the development of obesity (Boynton-Jarrett et al, 2012, D'Argenio et al, 2009, Gunstad et al, 2006 and psychiatric disorders (Breslau, 2002, Chou, 2012.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The psychiatric disorders of the subjects who responded to this survey are those usually reported by the victims of sexual violence but their prevalence is a little higher than that of published epidemiological studies [1,2,4].…”
Section: Discussionmentioning
confidence: 57%
“…Several studies have focused on the long term effects of sexual violence that may occur at a distance from the initial trauma throughout the life of the victim. It is well established that child sexual abuse, like other forms of mistreatment, is associated with psychiatric and behavioral disorders such as depression, personality disorders, eating disorders, substance abuse [1][2][3][4]. The prevalence of chronic pain is also increased among victims, whether it is musculoskeletal or pelvic pain and headache [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%